A Hierarchical Sub-Chromosome Genetic Algorithm (Hsc-ga) to Optimize Power Consumption and Data Communications Reliability in Wireless Sensor Networks - Hosseini, Elahe S.; Esmaeelzadeh, Vahid; Eslami, Motahhareh (Wireless personal communications, 2015)
High reliability and low power consumption are among the major requirements in design of wireless sensor networks (WSNs). In this paper, a multi-objective problem is formulated as a Joint Power consumption and data Reliability (JPR) optimization problem. For this purpose, a connected dominating set (CDS)-based topology control approach is proposed. Our objective is to self-organize the network with minimum interference and power consumption. We consider the power changes into a topology with minimum CDS infrastructure subject to connectivity constraints. Since this problem is NP-hard, it cannot be dealt with using polynomial-time exact algorithms. Therefore, we first present a genetic algorithm taking into consideration problem-specific goals and constraints in an approximated manner called JPR Genetic Algorithm ( Jpr - ga ). Secondly, a Hierarchical Sub-Chromosome Genetic Algorithm ( Hsc - ga ) is proposed to obtain more accurate and faster solutions in the large and dense networks. We evaluate these algorithm over different networks topologies to analyse their efficiency. Comparing Jpr - ga and Hsc - ga with two different scenarios reveal that the proposed algorithms can efficiently balance power consumption and data communication reliability of sensor nodes and also prolong the network lifetime in WSNs.